Microplastics: What Drinking Water Utilities Need to Know. Issue 11 (4th November 2019) - Smith, Emily; Dziewatkoski, Michael; Henrie, Tarrah; Seidel, Chad; Rosen, Jeffrey
Key Takeaways: Consumers are becoming more concerned with microplastics in water, so utilities should start thinking about methods to identify and address them. Although there is a lot of research on microplastics in marine environments, there isn't much research yet with drinking water. To address microplastics, utilities should establish sampling and analytical techniques, identify treatment methods, and implement communications strategies.